Soil abiotic and biotic properties constrain the establishment of a dominant temperate tree into boreal forests. (12th January 2020) - Carteron, Alexis; Parasquive, Vlad; Blanchard, Florence; Guilbeault‐Mayers, Xavier; Turner, Benjamin L.; Vellend, Mark; Laliberté, Etienne
Abstract: Climate warming is expected to cause the poleward and upward elevational expansion of temperate plant species, but non‐climatic factors such as soils could constrain this range expansion. However, the extent to which edaphic constraints on range expansion have an abiotic (e.g. soil chemistry) or biotic (e.g. micro‐organisms) origin remains undetermined. We conducted greenhouse experiments to test if the survival and growth of a major North American temperate tree species, Acer saccharum (sugar maple), is independently or jointly constrained by abiotic and biotic properties of field‐collected soils from within and beyond the species' elevational range. Abiotic factors, particularly low base cation concentrations, were major constraints to seedling establishment in boreal forest soils (beyond the range edge), but insufficient arbuscular mycorrhizal fungal inoculum (biotic factor) also strongly reduced seedling performance in these soils. Synthesis. Our results suggest that forecasting future changes in forest composition under climate warming requires consideration of soil properties as well as the mycorrhizal status of tree species. Abstract : Plant establishment in a new habitat can be mediated by soil‐related abiotic and biotic factors. Our study shows that unfavourable soil chemistry and lack of beneficial mycorrhizal fungi in boreal forests greatly diminished the potential survival and growth of sugar maple seedlings. Predicting future changes in forest composition under climate warming will require consideration of soil properties as well as the mycorrhizal status of tree species. Translated Abstract: Résumé Le réchauffement climatique devrait entraîner l'expansion des espèces tempérées vers les pôles et en altitude, mais des facteurs non‐climatiques pourraient limiter cette expansion. Les sols en particulier pourraient potentiellement contraindre l'expansion des essences tempérées dans les forêts boréales à cause de propriétés édaphiques biotiques (micro‐organismes p. ex.) et/ou abiotiques (propriétés chimiques p. ex.). Dans cette étude, nous avons mené des expériences en serre utilisant des manipulations et traitements de sols frais récoltés sur le terrain. Nous avons ainsi testé si l'établissement, dans la forêt boréale, d'une espèce d'arbre dominante en forêt tempérée d'Amérique du Nord ( Acer saccharum ) est limitée par les propriétés édaphiques. Nous avons évalué le rôle joué par les micro‐organismes et la chimie du sol sur la survie, la biomasse et la performance globale des semis. Les facteurs abiotiques tels que de faibles concentrations en cations pourraient constituer des contraintes édaphiques importantes à l'établissement d' Acer saccharum au‐delà de son aire de répartition, mais aussi les facteurs biotiques tel que le faible potentiel d'inoculum de champignons mycorhiziens arbusculaires dans les sols boréaux. Nos résultats suggèrent que la prévision des changements futurs dans la composition de la forêt sous l'effet du réchauffement climatique nécessite de prendre en compte les propriétés édaphiques, ainsi que les traits souterrains des arbres tels que leur stratégie mycorhizienne.